Eksperimentasi Model Pembelajaran Kooperatif Tipe Student Team Achievement Divisions (STAD) dan Think Pair Share (TPS) Terhadap Prestasi Belajar Matematika Ditinjau Dari Motivasi Berprestasi - Untari, Erny (Universitas Islam Raden Intan Lampung, INDONESIA, 2017)
The purposes of this study are to determine: (1) which one have a better mathematics achievement, students who taught by cooperative learning model STAD or TPS type. (2) which one have a better mathematics achievement, students who have high, middle, or low achievement motivation. (3) is there any interaction between learning model and achievement motivation towards mathematics achievement. This study is a quasi experimental research with 2x3 factorial design. The population of this study is all students XI Grade SMA N 1 Kwadungan in academic year 2016/2017. Sampling was done by random technique. The total of sample is 28 students, with details of 14 students for class experiment one and 14 students for class experiment two. The instruments used to collect data are test of prior knowledge in mathematics, achievement motivation questionnaire and mathematics achievement test. The trial of test instrument includes content validity, difficulty level, discrimination power, and reliability. The testing of hypothesis uses two-way analysis of variance with unequal cell. The testing of hypothesis concludes that (1) Students who taught by cooperative learning model of TPS type have better mathematics achievement than students who taught by cooperative learning model of STAD type. (2) Students who have high achievement motivation have better mathematics achievement than students who have middle and low achievement motivation, also students who have middle achievement motivation have better mathematics achievement than students who have low achievement motivation. (3) There isn’t interaction between learning model and achievement motivation towards mathematics achievement.